EVIDENCE-BASED PROTOCOLS: Into the Home Healthcare Setting - Beissner, Katherine L. (Home Healthc Now, 2017)
Activity-limiting pain is common among older home care patients and pain management is complicated by the high prevalence of physical frailty and multimorbidity in the home care population. A comparative effectiveness study was undertaken at a large urban home care agency to examine an evidence-based pain self-management program delivered by physical therapists (PTs). This article focuses on PT training, methods implemented to reinforce content after training and to encourage uptake of the program with appropriate patients, and therapists’ fidelity to the program. Seventeen physical therapy teams were included in the cluster randomized controlled trial, with 8 teams (155 PTs) assigned to a control and 9 teams (165 PTs) assigned to a treatment arm. Treatment therapists received interactive training over two sessions, with a follow-up session 6 months later. Additional support was provided via emails, e-learning materials including videos, and a therapist manual. Program fidelity was assessed by examining PT pain documentation in the agency’s electronic health record. PT feedback on the program was obtained via semistructured surveys. There were no between-group differences in the number of PTs documenting program elements with the exception of instruction in the use of imagery, which was documented by a higher percentage of intervention therapists (p = 0.002). PTs felt comfortable teaching the program elements, but cited time as the biggest barrier to implementing the protocol. Possible explanations for study results suggesting limited adherence to the program protocol by intervention-group PTs include the top-down implementation strategy, competing organizational priorities, program complexity, competing patient priorities, and inadequate patient buy-in. Implications for the implementation of complex new programs in the home healthcare setting are discussed.